Microstructural and Electrical Characterization of Plasma Sprayed Cu‐Mn Oxide Spinels as Coating on Metallic Interconnects for Stacking Solid Oxide Fuel Cells1. Issue 5 (3rd September 2015) - Spotorno, R.; Piccardo, P.; Perrozzi, F.; Valente, S.; Viviani, M.; Ansar, A.; Christiansen, Niels; Hagen, Anke; Bele, Petra; Bucheli, Olivier
Abstract Interconnect coatings are extremely important to ensure an optimal performance of a solid oxide fuel cell (SOFC) stack. Nowadays the most common material used to produce SOFC interconnects is a ferritic stainless steel (FSS) rich in chromium which is much less expensive than the previously used ceramic interconnects. Nevertheless interconnects have to be coated in order to provide protection from the aggressive environment that surrounds them and reduce chromium species migration to the cell's cathode. In this work three different coatings were applied to Crofer® 22 H substrates via atmospheric plasma spraying (APS): two different stoichiometries of copper manganese oxide (CuxMn3–xO4, where x = 1.4 and 1.5) and one of cobalt manganese oxide (CoxMn3–xO4, where x = 1.5), considered the state of the art coating for SOFC interconnects. X‐ray diffraction (XRD) was used to check the composition of deposited layers. Area specific resistance (ASR) of samples has been characterized for different samples in the range 673–1, 073 K and during a 100 hours ageing test at 1, 073 K. Microstructural changes and Cr‐barrier properties have been characterized by SEM‐EDX analyses.